The Effectiveness Of Training Matrix Applications For Onboard Safety Culture Practices: A Case Study In Oil & Gas Floating Facilities - Maria Ulfa, Fua'di (Universiti Malaysia Sarawak (UNIMAS), 2020)
Training matrix implementation had been conducted all over countries even though the effectiveness of the matrix had not been proved yet. This study explored the effectiveness of training matrix implementation for onboard safety culture practice. A sample of 8 informants from an oil and gas floating facilities were recruited using purposive sampling. The criteria that had been set were employee that involve in FPSO operation and maintenance service, employee onboard, and employee that went for training more than 3 times in the past 3 years scheduled by the organization. The informants had been interviewed using semi-structured interview. The findings had been analyzed using content analysis and found that the experience shared by the informants showed that the training matrix arrangement fulfilled the utilization of ADDIE model framework. The advantages supported the past findings which mentioned that the implementation enhance competency, relate to job functions, help in career development, and keep updated with the latest requirement. This study discovered new findings which mentioned that the matrix implementation helps in minimizing cause of failure. As the matrix follows the job function and helps in competency enhancement, it ensures that the employees are competent and certified enough to work onboard. Hence, the cause of failure can be minimized, and the safety culture practice in the organization can be improved.